Optimal Spatial Organisation of the Regional Economy: Search for Parameters and Dependencies - Lavrikova, Yuliya G.; Suvorova, Arina V. (Economy of Regions, 2020)
The framework guiding the spatial development of the Russian Federation is widely discussed. However, the characteristics of an optimally organised space are yet to be defined. This research focuses on one of the aspects of this problem, aiming to identify the characteristics of the optimal spatial organisation of the regional economy depending on the degree of homogeneity of socio-economic space. We examined four Russian regions comparable in area and administrative-territorial division, but differing in economic activity (Krasnodar Krai, the Republic of Tatarstan, Chelyabinsk Oblast and Kemerovo Oblast). For that purpose, we applied spatial analysis methods: spatial autocorrelation, cartographic analysis. The examined regions are characterised by varying degrees of spatial heterogeneity. It is most significant in the Chelyabinsk Oblast, where 46 % of the population lives in the territory of two municipalities that produce 73 % of the regional products. The territories of Chelyabinsk Oblast differ the most in terms of output (R/P is 994.65). The degree of heterogeneity is also high in the Republic of Tatarstan, characterised by the differentiation of municipalities in terms of inhabitants (the maximum R/P is 42.09) and fragmentation of space (the global Moran’s index for the considered parameters is less than its expected value). Krasnodar Krai is the most homogeneous (the production R/P is 131.57, the settlement R/P is 14.52) and integrated territory (spatial autocorrelation is positive). Simultaneously, there is no clear relationship between the degree of spatial homogeneity and the efficiency of economic activity in the regions in the short term. The results show that it is impossible to use a single unified model for the development of various territories. Thus, it is necessary to apply a differentiated approach when determining spatial development guidelines. The obtained results can be used by public authorities in the field of spatial development management. Moreover, they can be used for further research of other parameters of spatial organisation that are not related to its homogeneity.